Comparative Efficacy of Chinese Herbal Injections for Treating Pediatric Bronchopneumonia: A Bayesian Network Meta-Analysis of Randomized Controlled Trials. (23rd May 2020) - Duan, Xiaojiao; Wang, Haojia; Wu, Jiarui; Guo, Yubo; Wang, Kaihuan; Liu, Xinkui; Xiantao, Zeng; Zhang, Xiaomeng
Abstract : Introduction . Pediatric bronchopneumonia is one of the common respiratory diseases in pediatrics. Chinese herbal injections (CHIs) are widely used to treat pediatric bronchopneumonia. In this study, we examined the efficacy of CHIs in the treatment of pediatric bronchopneumonia using a network meta-analysis (NMA). Methods . Randomized controlled trials (RCTs) of CHIs combined western medicine (WM) versus WM were searched from electronic databases. WinBUGS 1.4.3 and Stata 13.0 were adopted to compute calculations and prepare graphs, respectively. Results . 168 RCTs with 21917 patients were included. The results revealed that Xixinnao injection (XXN) + WM had the most probability to be the best intervention in the four aspects of rate of clinical efficacy, antipyretic time, cough disappearance time, and lung shadow disappearance time. While as to lung shadow disappearance time, asthma disappearance time, and hospitalization time, Yanhuning injection (YHN) + WM could be the best intervention. The safety of CHIs needs to be further assessed. Conclusions . Based on this NMA, XXN + WM and YHN + WM were potential optimal therapies in pediatric bronchopneumonia, and their safety should be strictly monitored.